A qualitative exploration of how young men in the UK perceive and experience informal help-seeking for mental health difficulties. (June 2022) - Burke, Lauren; John, Mary; Hanna, Paul
Highlights: Young males are least likely to seek support for mental health problems and this has been shown to have adverse consequences. There is a paucity of literature exploring how young men experience seeking help from informal sources (e.g., family, friends). This study interviewed fourteen adolescent males, aged 16–18 and used thematic analysis to analyse data. Themes explore how familiarity, masculinities, stigma, and emotional burden are experienced in informal relationships. Findings show the socio-cognitive, systemic and individual factors that influence how young men seek support informally. Abstract: Background: Despite having a similar prevalence of mental health problems to adolescent females, adolescent males do not seek support for mental health difficulties at the same rate. Extensive research has highlighted the many barriers and facilitators for seeking support professionally. However, there is a paucity of qualitative research that explores how young males seek support from informal sources of support. This study aims to explore the proximity and intersubjectivity of informal relationships that young men possess and considers the impact on thoughts and experiences of help-seeking for mental health difficulties. Method: Using a qualitative approach, fourteen young males aged 16 to 18 years were recruited to participate in one-to-one semi-guided interviews. Interview data was analysed using thematic analysis. Results: Two key themes were identified: 1) Proximity and familiarity, 2) Navigating feared outcomes and remaining silent. These two themes explore in-depth how notions of perceived familiarity, masculinities, stigma, trust, and emotional burden are experienced in relation to the various proximal relationships that these young men hold. The themes explore the array of intricacies and dynamics perceived within proximal relationships, and the implications for seeking support from these sources, in relation to family, friends, and teachers. Conclusion: The findings illustrate the complexities of informal relationships that young males possess as well as the socio-cognitive, systemic, individual, and structural factors that influence help-seeking behaviour from these sources. The considerations that young men undertake must be understood to address the disparities in help-seeking behaviours for mental health problems. Future research should consider how ethnicity, culture, and socioeconomic background influences how young men seek help from informal sources of support.